Земля обетованная - Мураками Харуки (Великие романы XX века, 2007)
Экземпляры: ф.14 (2007) / Инвентарный номер: 51011 / Цена: / Сис.шифр: 84(5Япо)-4 / Авт.знак: М 91 / ГРНТИ: 17.82.31 / ББК: 84(5Япо)-44